Relying on pulse oximetry to avoid hypoxaemia and hyperoxia: A multicentre prospective cohort study in patients with circulatory failure. Issue 3 (May 2023) - Boulain, Thierry; Nay, Mai-Anh; Dequin, Pierre-François; Lascarrou, Jean-Baptiste; Vignon, Philippe; Kamel, Toufik; Muller, Grégoire; Ehrmann, Stephan; ,; Baudin, Olivier; Calvat, Sylvie; Cracco, Christophe; et al.
Abstract: Purpose: The purpose of this study was to assess the predictive performance of pulse oximetry (SpO2 ) to rule out hypoxaemia and hyperoxia in critically ill patients. Methods: SpO2, arterial oxygenation (SaO2 ), and arterial partial pressure of oxygen (PaO2 ) were prospectively and simultaneously measured every 6 h during the first 24 h of intensive care unit admission in a multicentre cohort of critically ill patients suffering acute circulatory failure. Likelihood ratios associated with different cutoff values of SpO2 to rule out hypoxaemia (SaO2  < 90% or PaO2  < 60 mmHg) or hyperoxia (SaO2  > 95% or PaO2  > 100 mmHg) and post-test probabilities were calculated. Mean bias between SpO2 and SaO2 and agreement interval were calculated. Area under the receiver operating characteristics associated with SpO2 to predict different threshold values of SaO2 and PaO2 were calculated. Results: Five hundred seventy-one patients (mean [standard deviation] Simplified Acute Physiology Score II: 58.7 [20.1]; mechanically ventilated 75.6%) with 2643 available SaO2 and PaO2 samples and corresponding 2643 SpO2 values were analysed. Mean bias between SpO2 and SaO2 was 1.1%, and its agreement interval ranged from −8.2 to +11.1%. SpO2 cutoff values of 88%, 90%, and 92% left the possibility that 8%–13% of patients had hypoxaemia. SpO2 < 95% left the possibility that 31% of patients had hyperoxia. All calculated areas under the receiver operating characteristics showed a lower limit of their 95% confidence interval below 0.85 Conclusion: In this cohort of patients with circulatory failure, SpO2 had poor discriminative ability to rule out hypoxaemia and hyperoxia. Overconfidence upon SpO2 monitoring may be dangerous.